1995
DOI: 10.1161/01.cir.91.9.2378
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Repolarization and Refractoriness During Programmed Electrical Stimulation in the Human Right Ventricle

Abstract: Repetitive extrastimulation not only shortens APD and subsequently ERP but also alters the ERP/APD relation by allowing capture to occur at progressively less complete repolarization levels. This progressive encroachment onto the preceding repolarization phase is associated with impaired impulse propagation and a high incidence of VT induction. This may help explain how repetitive, closely coupled extrastimulation induces ventricular tachycardia in the human heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 29 publications
9
73
2
Order By: Relevance
“…As expected from previous studies, 13,14,29 PRR was not observed in the absence of sodium channel-blocking drugs. On the contrary, during baseline, repetitive extrastimulation caused the ERP to shorten by a greater extent than the concomitant APD 90 .…”
Section: Postrepolarization Refractorinesssupporting
confidence: 90%
See 2 more Smart Citations
“…As expected from previous studies, 13,14,29 PRR was not observed in the absence of sodium channel-blocking drugs. On the contrary, during baseline, repetitive extrastimulation caused the ERP to shorten by a greater extent than the concomitant APD 90 .…”
Section: Postrepolarization Refractorinesssupporting
confidence: 90%
“…14 In this isolated heart study, as in the previous human heart study, 14 encroachment of repetitive extrastimuli, or burst stimuli, onto the repolarization phase of the preceding action potential was associated with tachyarrhythmia induction (Figure 6). This may be explained by the fact that these most premature responses originated during the phase of relative refractoriness and therefore had slower conduction velocities (Table 2), resulting in shortened excitation wavelengths and subsequently functional reentry arrhythmias.…”
Section: Postrepolarization Refractorinesssupporting
confidence: 60%
See 1 more Smart Citation
“…20, 36 The amplitude of the MAP recording declines gradually over the study. 37 However, the APD restitution curve recorded with the MAP electrode closely resembles the APD restitution curve obtained by the microelectrode technique. 38 A second limitation is that only APD restitution from the RVOT was measured, making determination of spatial heterogeneity of APD restitution inapplicable.…”
Section: Study Limitationssupporting
confidence: 66%
“…A substantial proportion of sudden cardiac arrests, approximately half in a recent study,2 are associated with ventricular tachycardia (VT) or ventricular fibrillation (VF). It has been observed clinically that sustained VT and VF are often preceded by several irregularly timed premature complexes,3, 4 and studies conducted to explore this phenomenon have shown that specific coupling interval patterns of premature complexes, such as short‐long‐short5 and short‐short‐short,6 tend to lead to reentry and VT. Various researchers have examined the mechanism by which premature complexes or pacing history can interact with electrical restitution properties, including the dependence of action potential duration (APD) and conduction velocity (CV) on the preceding diastolic interval (DI) to produce dynamical heterogeneity of refractoriness, wave break, reentry, and VF7, 8, 9, 10, 11 (see elsewhere12, 13 for reviews).…”
Section: Introductionmentioning
confidence: 99%